Pengaruh Konten Instagram Terhadap Pemenuhan Kebutuhan Informasi Followers @Wonosobozone - Nisrina Fajari; Diana Khuntari (Lembaga Pengembangan Kinerja Dosen, 2023)
Currently Instagram is developing into a platform for exchanging information. Many users use Instagram to share information, as well as find information. The Instagram account @wonosobozone is one of the accounts that provides local information content about Wonosobo Regency. The Instagram account @wonosobozone also uploads national and international news with various rubrics. All information uploaded by the Instagram account @wonosobozone in an interesting way in the form of feed, story, and video content (reels and IGTV). The purpose of this research is to determine whether there is an effect of the content of the @wonosobozone Instagram account on meeting the information needs of followers. This study uses the concept of information needs and Instagram content which includes feed posts, stories, story highlights, IGTV videos, and guides. The research uses quantitative methods. The research sample was taken from 100 respondents who are followers of the Instagram account @wonosobozone with a random sampling technique. Data collection is done by distributing questionnaires to Instagram followers @wonosobozone. The data analysis techniques used in this study were normality test, correlation test, simple linear regression test, coefficient of determination test and hypothesis testing using SPSS 25. The results of the study prove that @wonosobozone's Instagram content has a significant influence on meeting the information needs of followers by 68,3%. While the remaining 31,7% is influenced by other factors not discussed in this study.